The Niruktalochanum : a guide to Jaska's Nirukta - Bhaṭṭācārya, Satyavrata Sāmaśramī (SAMP early 20th-century Indian books project ;, 1907)
Study of the Nirukta of Yāska, classical treatise on Vedic philology and synonyms.